1999
DOI: 10.4319/lo.1999.44.6.1388
|View full text |Cite
|
Sign up to set email alerts
|

Sedimentation of copepod fecal material in the coastal northern Baltic Sea: Where did all the pellets go?

Abstract: We investigated the sedimentation of copepod fecal pellets in three different sea areas representing a sheltered bay, an archipelago area, and the open sea on the southwestern coast of Finland in the northern Baltic Sea. Fecal carbon sedimentation was always Ͻ0.05% of the total sedimentation of particulate organic carbon, whereas the fecal carbon production (estimated from copepod abundance, assuming production rate of 10 pellets copepod Ϫ1 d Ϫ1) contributed to 4-17% of particulate organic carbon sedimentation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
36
2

Year Published

2001
2001
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(46 citation statements)
references
References 55 publications
6
36
2
Order By: Relevance
“…These estimates are somewhat higher than the published values from the area (9-22 pellets m 22 d 21 ; Viitasalo et al 1999). However, Viitasalo et al concluded that less than 1% of copepod fecal pellets sedimented; most of them were probably broken up and decomposed in the water column.…”
Section: Discussioncontrasting
confidence: 54%
“…These estimates are somewhat higher than the published values from the area (9-22 pellets m 22 d 21 ; Viitasalo et al 1999). However, Viitasalo et al concluded that less than 1% of copepod fecal pellets sedimented; most of them were probably broken up and decomposed in the water column.…”
Section: Discussioncontrasting
confidence: 54%
“…It has been hypothesised that removal by metazooplankton is the most likely fate of fecal material in the upper layers of the sea (Paffenhöfer & Knowles 1979, Lampitt et al 1990, González & Smetacek 1994, Viitasalo et al 1999) since bacteria alone can not be responsible for the majority of the remineralisation of freshly egested fecal pellets (Jacobsen & Azam 1984, Lampitt et al 1990. Support for this hypothesis is found in the few existing publications, which show that some copepod species do clear fecal pellets at high rates in the laboratory (Table 5).…”
Section: Ecological Implicationssupporting
confidence: 63%
“…The increasing clearance of fecal pellets with decreasing pellet size may also explain the higher vertical flux of fecal pellets observed when large Calanus species as opposed to small copepod species dominate the zooplankton community (González et al 1994a, Viitasalo et al 1999, Wassmann et al 2000. A high ratio of large calanoid to small cyclopoid copepods is generally related to a high vertical flux of fecal pellets and a low ratio to a low flux of pellets (González & Smetacek 1994, Svensen & Nejstgaard 2003.…”
Section: Ecological Implicationsmentioning
confidence: 97%
“…Pellet number was counted, and their average length and width were measured under a binocular microscope. Pellet volume was calculated assuming pellets to be cylinders with spherical ends (Viitasalo et al 1999). From each treatment, 200 pellets and various numbers of living copepods were frozen at -20°C for toxin analyses.…”
Section: Methodsmentioning
confidence: 99%
“…Zooplankton faecal pellets either sink to deep waters and sediment to the bottom (Turner & Ferrante 1979, Dagg & Walser 1986, Fowler et al 1991, or are recycled in the euphotic zone by other zooplankton (Frankenberg & Smith 1967, Smetacek 1980, Hofmann et al 1981, Lampitt et al 1990, Ayukai & Hattori 1992, Viitasalo et al 1999, reviewed by Turner 2002. If toxic pellets are recycled in the mixed layer, toxins may disperse further and accumulate in the pelagic food web.…”
Section: Introductionmentioning
confidence: 99%